Effects of different types of intermittent fasting on metabolic outcomes: an umbrella review and network meta-analysis - Yu-En Chen; Hui-Li Tsai; Yu-Kang Tu; Ling-Wei Chen (BMC Medicine)
Abstract Background Intermittent fasting (IF) holds promise for enhancing metabolic health. However, the optimum IF forms and their superiority over continuous energy restriction (CER) remain unclear due to disconnected findings. Methods We systematically searched PubMed, Embase, and the Cochrane databases for meta-analyses of randomized controlled trials (RCTs) investigating the association between IF and metabolic health outcomes. Subsequently, we performed an umbrella review and network meta-analysis (NMA) to evaluate the efficacy of different forms of IF (time-restricted eating (TRE), alternate-day fasting (ADF), and 5:2 diet (regular eating for 5 days and energy restriction for 2 days per week)) compared to CER and usual diets on metabolic health outcomes. To assess the certainty of both direct and indirect estimates, we employed the Confidence in Network Meta-Analysis (CINeMA) approach. Additionally, we calculated the surface under the cumulative ranking curve (SUCRA) for each dietary strategy to determine their ranking in terms of metabolic health benefits. Results Ten of the best and non-redundant meta-analysis studies, involving 153 original studies and 9846 participants, were included. When considering direct evidence only, all IF forms significantly reduced body weight compared to usual diets. In NMA incorporating indirect evidence, all IF regimens also significantly reduced body weight compared to usual diets. In the SUCRA of NMA, IF ranked higher than usual diets or CER in 85.4% and 56.1% of the outcomes, respectively. ADF had the highest overall ranking for improving metabolic health (ranked first: 64.3%, ranked second: 14.3%). Conclusions Overall, all IF forms demonstrate potentials to improve metabolic health, with ADF appearing to produce better outcomes across investigated outcomes. Further high-quality trials are warranted to confirm the (relative) efficacy of IF on metabolic health. Trial registration PROSPERO (record no: CRD42022302690).